Morphological and functional properties distinguish the substance P and gastrin-releasing peptide subsets of excitatory interneuron in the spinal cord dorsal horn. Issue 2 (February 2019) - Dickie, Allen C.; Bell, Andrew M.; Iwagaki, Noboru; Polgár, Erika; Gutierrez-Mecinas, Maria; Kelly, Rosalind; Lyon, Heather; Turnbull, Kirsten; West, Steven J.; Etlin, Alexander; Braz, Joao; Watanabe, Masahiko; et al.
Abstract : Abstract: Excitatory interneurons account for the majority of neurons in the superficial dorsal horn, but despite their presumed contribution to pain and itch, there is still limited information about their organisation and function. We recently identified 2 populations of excitatory interneuron defined by expression of gastrin-releasing peptide (GRP) or substance P (SP). Here, we demonstrate that these cells show major differences in their morphological, electrophysiological, and pharmacological properties. Based on their somatodendritic morphology and firing patterns, we propose that the SP cells correspond to radial cells, which generally show delayed firing. By contrast, most GRP cells show transient or single-spike firing, and many are likely to correspond to the so-called transient central cells. Unlike the SP cells, few of the GRP cells had long propriospinal projections, suggesting that they are involved primarily in local processing. The 2 populations also differed in responses to neuromodulators, with most SP cells, but few GRP cells, responding to noradrenaline and 5-HT; the converse was true for responses to the μ-opioid agonist DAMGO. Although a recent study suggested that GRP cells are innervated by nociceptors and are strongly activated by noxious stimuli, we found that very few GRP cells receive direct synaptic input from TRPV1-expressing afferents, and that they seldom phosphorylate extracellular signal–regulated kinases in response to noxious stimuli. These findings indicate that the SP and GRP cells differentially process somatosensory information. Abstract : Supplemental Digital Content is Available in the Text.Superficial dorsal horn excitatory interneuron populations, as identified by neuropeptide expression, differ in morphological, electrophysiological, and pharmacological properties. This has implications for understanding pain processing.